2019
DOI: 10.1002/hpm.2806
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing inappropriate magnetic resonance imaging (MRI) prescriptions and resulting economic burden on patients suffering from back pain

Abstract: Summary Introduction Back pain is a common global disorder and magnetic resonance imaging (MRI) is one method of assessing its cause. The lack of official and general clinical guidelines is the cause of inadequate supervision of lumbar MRI prescriptions. The goal of this research was to analyze inappropriate lumbar MRI prescriptions and the resulting economic burden on individuals. Method This is a descriptive‐analytical study carried out on a sample of 614 patients who visited four hospitals in Tehran. The ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…In a study by Ebrahimipour et al (18), out of 115 knee MRI prescriptions, 63 (54.800 %) were incorrect. Several studies in Iran have focused on prescriptions without indication (19,20,21). Kavosi et al (19) reported that 21 percent of brain MRI prescriptions were inappropriate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by Ebrahimipour et al (18), out of 115 knee MRI prescriptions, 63 (54.800 %) were incorrect. Several studies in Iran have focused on prescriptions without indication (19,20,21). Kavosi et al (19) reported that 21 percent of brain MRI prescriptions were inappropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Kavosi et al (19) reported that 21 percent of brain MRI prescriptions were inappropriate. Jahanmehr et al (20) reported that 39.700 % of lumbar MRI was inappropriate. In a study conducted by Salari et al (21), 56 percent of lumbar spine prescriptions were incorrect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 With the increase in the number of requested MRI exams, it has been documented that between 10% and 50% of these exams are considered as unwarranted (or unnecessary) requests. 7 The majority of unnecessary MRIs are for lumbar spine 8 and knee pain complaints. 9 Many patients suffering from low back pain (LBP) or knee pain are routinely referred for MRI prior to having a specialist consultation.…”
Section: Introductionmentioning
confidence: 99%
“…9 Many patients suffering from low back pain (LBP) or knee pain are routinely referred for MRI prior to having a specialist consultation. 7 However, diagnostic imaging guidelines do not recommend MRI as a routine imaging procedure in these cases. 8 For patients with moderate to severe knee osteoarthritis (OA) and degenerative changes, evidence-based guidelines recommend a thorough clinical examination supplemented by weightbearing radiographs over a knee MRI scan in showing degenerative changes.…”
Section: Introductionmentioning
confidence: 99%